Augmented reality based application using Vizard / Nurul 'Ain Ramli - Ramli, Nurul 'Ain (2011)
This project focus on the development of a set of Malay Kuih Muih in 3D based on Augmented Reality Technologies and the integration into an application in effort to preserve and promote the Kuih Muih. It is known that Kuih is one of the very unique delicacies that have never been preserved or promoted through a wonderful world of 3D.People usually put the main priority on preserving the historical and cultural objects, artifacts and monuments. Therefore a set of selected Malay Kuih Muih has been designed and created in 3D model to apply the Augmented Reality Technologies on to them as an effort to preserve and promote the Kuih Muih in an application. The application is designed based on the Augmented Reality Technologies using Vizard. It is tangible, easy to be recognized by the user and very interactive. It contains information about the originality of the Kuih Muih and their recipes.